A Review on Risk Factors in the Project of Oil and Gas Industry - Rodhi, Nova Nevila; Anwar, Nadjadji; Artama Wiguna, I Putu (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
In Each activity in the oil and gas industry there are risks that could hamper the project and also there is a huge risk to the environment, social and economic. Besides oil and gas industry projects also have the potential to be dangerous to life, property and the environment, the hazard can occur if the activity is not controlled and regulated by appropriate. Basically, the disaster is certainly not possible to be planned and can occur at any time. But the circumstances of a disaster can be anticipated, that is the way to plan preventive measures and control.Based on the description above, this paper aims to discuss risk factors and risk assessment techniques that can help sustainable development programs. From the results of this study note that the risk factors of projects in the oil and gas industry is very complex, so a risk analysis must be done from various aspects, namely the project itself, the environment and disaster and should be integrated with aspects of sustainable development. As for the suggested technique is a combination of monte carlo and system dynamics.